Eksistensi Perempuan Berdaya dalam Drama Seri Korea “The World of the Married” - ROSMALINA, IDA; Zuriyati, Zuriyati; Rohman, Saifur (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2024)
Determining existence is the personal duty of a human being. Unfortunately, this notion of self-existence is often 'lost' when associated with women. The patriarchal system has weakened the position of women because they are always seen as domestic creatures and helpless. Existential feminism has contributed to the women's movement to determine their own destinies, one of which is to become empowered women. This study uses a descriptive method using an existentialist feminism approach. As for the source of data from this study, the Korean drama entitled The World of The Married was taken. The writer is interested in studying the drama series The World of The Married because this series presents the main female character who can maintain their existence as an empowered woman in a patriarchal society.